Implementation of Delayed Cord Clamping for 3 Min During Term Cesarean Sections Does Not Influence Maternal Blood Loss - Stefanie Celen; Stefanie Celen; Emily J. J. Horn-Oudshoorn; Ronny Knol; Eline C. van der Wilk; Irwin K. M. Reiss; Philip L. J. DeKoninck (Frontiers Media S.A., 2021)
Background: To assess maternal safety outcomes after a local protocol adjustment to change the interval of cord clamping to 3 min after term cesarean section.Design, Setting, and Patients: A retrospective cohort study in a tertiary referral hospital (Erasmus MC, Rotterdam). We included pregnant women who gave birth at term after cesarean section. A cohort (Nov 2016-Oct 2017) prior to the protocol implementation was compared to a cohort after its implementation (Nov 2017-Nov 2018). The study population covered 789 women (n = 376 pre-cohort; n = 413 post-cohort).Interventions: Implementation of a local protocol changing the interval of cord clamping to 3 min in all term births.Main outcome measures: Primary outcomes were the estimated maternal blood loss and the occurrence of postpartum hemorrhage (blood loss >1,000 ml). Secondary outcomes included both maternal as well as neonatal outcomes.Results: Estimated maternal blood loss was not significantly different between the pre-cohort and post-cohort (400 mL [300-600] vs. 400 mL [300-600], p = 0.52). The incidence of postpartum hemorrhage (26 [6.9%] vs. 35 (8.5%), OR 1.24, 95% CI 0.73-2.11) and maternal blood transfusion (9 [2%] vs. 13 (3%), OR 1.33, 95% CI 0.56-3.14) were not different. Hemoglobin change was significantly higher in the post-cohort (−0.8 mmol/L [−1.3 to −0.5] vs. −0.9 mmol/L [−1.4 to −0.6], p = 0.01). In the post-cohort, neonatal hematocrit levels were higher (51 vs. 55%, p = 0.004) and need for phototherapy was increased (OR 1.95, 95% CI 0.99-3.84).Conclusion: Implementation of delayed cord clamping for 3 min in term cesarean sections was not associated with increased maternal bleeding complications.